The role of children's theater scenography on the representative and recipient child (Journal of the College of Basic Education, 2023)
The children's theater is an integral part of the traditional theater, and one of the important messages in the upbringing and education of children.children, as well as entertaining and entertaining them in a dramatic manner that the child can comprehend. “The child receives information through live action, as he participates emotionally with what is presented to him.on the stage of situations that affect his daily life, his activities and his desires, as every theatrical imageHe watches it during the show, receives it and interprets it through his sensory perceptions, on which he relies more.